An Agenda for Open Science in Communication. (17th February 2020) - Dienlin, Tobias; Johannes, Niklas; Bowman, Nicholas David; Masur, Philipp K; Engesser, Sven; Kümpel, Anna Sophie; Lukito, Josephine; Bier, Lindsey M; Zhang, Renwen; Johnson, Benjamin K; Huskey, Richard; Schneider, Frank M; et al.
Abstract: In the last 10 years, many canonical findings in the social sciences appear unreliable. This so-called "replication crisis" has spurred calls for open science practices, which aim to increase the reproducibility, replicability, and generalizability of findings. Communication research is subject to many of the same challenges that have caused low replicability in other fields. As a result, we propose an agenda for adopting open science practices in Communication, which includes the following seven suggestions: (1) publish materials, data, and code; (2) preregister studies and submit registered reports; (3) conduct replications; (4) collaborate; (5) foster open science skills; (6) implement Transparency and Openness Promotion Guidelines; and (7) incentivize open science practices. Although in our agenda we focus mostly on quantitative research, we also reflect on open science practices relevant to qualitative research. We conclude by discussing potential objections and concerns associated with open science practices.